2019
DOI: 10.1002/cam4.2776
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GMDS‐AS1 inhibits lung adenocarcinoma development by regulating miR‐96‐5p/CYLD signaling

Abstract: According to the global cancer statistic, lung cancer is one of the most dangerous tumors, which poses a serious threat to human health. Exploration the mechanism of lung cancer and new targeted therapeutic measures is always the hot topic. Long noncoding RNA (lncRNA) is an important factor affecting the development of tumors. However, the research on the mechanism of lncRNA in the progress of lung cancer needs to be further expanded. In this study, we found that the expression of lncRNA GMDS‐AS1 was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…We have previously reported that LINC02323 and another five lncRNAs (LINC01819, ZNF649-AS1, HNF4A-AS1, FAM222A-AS1 and LINC00672) could be used as both a marker of metastasis and a predictor for poor prognosis in LUAD patients. 16 In the present study, our data showed that LINC02323 silencing markedly inhibited the migration and invasion of SPC-A-1 cells, while LINC02323 overexpression significantly enhanced the migratory and invasive abilities of H1975 cells. We also proved that LINC02323 did not affect the proliferative ability of SPC-A-1 and H1975 cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We have previously reported that LINC02323 and another five lncRNAs (LINC01819, ZNF649-AS1, HNF4A-AS1, FAM222A-AS1 and LINC00672) could be used as both a marker of metastasis and a predictor for poor prognosis in LUAD patients. 16 In the present study, our data showed that LINC02323 silencing markedly inhibited the migration and invasion of SPC-A-1 cells, while LINC02323 overexpression significantly enhanced the migratory and invasive abilities of H1975 cells. We also proved that LINC02323 did not affect the proliferative ability of SPC-A-1 and H1975 cells.…”
Section: Discussionsupporting
confidence: 60%
“…[11][12][13][14][15] LncRNAs play essential roles in the migration, invasion and EMT and are discovered to act as miRNA sponges to participate in cancer progression. [16][17][18] Our previous study has shown that six lncRNAs, including LINC02323, are associated with metastasis and prognosis of LUAD. 19 Herein, we hypothesized that LINC02323-miRNA-target pathway might participate in the process of EMT and metastasis of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can play roles in regulating the expression level of target genes in a variety of malignant tumors, including lung cancer that has been reported in a large number of studies (14)(15)(16)(17)(18)(19)(20). Zhao et al (21) find that lncRNA GMDS-AS1 could act as ceRNA to upregulate the mRNA of CYLD by sponging miR-96-5p. In addition, the intervention of the GMDS-AS1/miR-96-5p/CYLD axis could regulate the growth and apoptosis of lung adenocarcinoma cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (21) find that lncRNA GMDS-AS1 could act as ceRNA to upregulate the mRNA of CYLD by sponging miR-96-5p. In addition, the intervention of the GMDS-AS1/miR-96-5p/CYLD axis could regulate the growth and apoptosis of lung adenocarcinoma cells (21). Yang et al (18) find that LCAT1 function as a ceRNA for miR-4715-5p, which leads to the upregulation of the activity of the endogenous target of miR-4715-5p, Rac family small GTPase 1 (RAC1).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have implicated lncRNAs in a range of genetic processes for gene expression modulation at epigenetic, transcriptional and post-transcriptional levels (11,12). In NSCLC, lncRNAs are frequently abnormally expressed and are involved in NSCLC occurrence and development (10)(11)(12)(13)(14). Hence, a detailed study of lncRNAs and their role in NSCLC may lead to unraveling potential targets to improve the prognosis and treatment of patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%